2010
DOI: 10.1111/j.1532-5415.2010.02904.x
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Influenza Vaccine Coverage in the United States, 2008

Abstract: Objective To determine the distribution of influenza vaccine coverage in the U.S. in 2008. Design, Setting, and Participants Cross-sectional analysis of the 2008 Behavioral Risk Factor Surveillance Survey (BRFSS). The BRFSS employs random-digit dialing to interview non-institutionalized adults in the U.S. and the territories. The sample was restricted to persons ≥50 years (N=249,723). Measurements Participants were asked if they had a flu shot during the past 12 months. Results In 2008, 42.0% of adults a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 27 publications
4
63
0
3
Order By: Relevance
“…46,47 These findings are mirrored in other studies that have examined challenges with vaccine uptake among racially and ethnically diverse minority communities. 48,49 Our findings reinforce the notion that maternal immunization is not likely to shift without effective, repeated messaging that normalizes vaccination as a women's and infant health protection issue. 50 With 80% of our sample expressing that they consider their OB/GYN to be their primary care physician, yet only 5% of them ever having received a vaccine from their OB/GYN, there is a unique opportunity presented to shift the targeted technologically driven messages delivered by our intervention toward more tailored practice-based messaging strategies in the future.…”
Section: Discussionsupporting
confidence: 75%
“…46,47 These findings are mirrored in other studies that have examined challenges with vaccine uptake among racially and ethnically diverse minority communities. 48,49 Our findings reinforce the notion that maternal immunization is not likely to shift without effective, repeated messaging that normalizes vaccination as a women's and infant health protection issue. 50 With 80% of our sample expressing that they consider their OB/GYN to be their primary care physician, yet only 5% of them ever having received a vaccine from their OB/GYN, there is a unique opportunity presented to shift the targeted technologically driven messages delivered by our intervention toward more tailored practice-based messaging strategies in the future.…”
Section: Discussionsupporting
confidence: 75%
“…Respondents with a primary care provider [12], at least some college education [17, 19], and a routine checkup [31] in the last 12 months had significantly higher odds of vaccination than those in the respective comparison groups. We also found that patients reporting cost as a barrier to seeing a physician in the last 12 months to be significantly associated with decreased odds of influenza vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to setting the goal of eliminating health disparities, Healthy people 2020 has set the target for influenza vaccination prevalence at 90 % for adults aged 65 and older and increased the target from 60 % to 90 % for high-risk non-institutionalized adults aged 18–64 [15]. While racial disparities in influenza vaccination have been reported [16, 17], most studies related to influenza vaccination and cancer survivors have not focused directly on race differences among cancer survivors and instead use individuals without cancer as the comparison group [10, 12, 1820]. Our study is the first, to our knowledge, to directly investigate racial disparities in influenza vaccination among cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Providing the public with facts about an emerging infectious disease episode is a necessary but insufficient step for containment. Public knowledge about infectious disease risk, experts' views about effectiveness of health-protective actions, or access to pharmaceutical interventions (e.g., vaccines) will not be the sole or even most significant determinants of health-protective behaviors during an emerging episode [22][23]. Risk perceptions and subjective appraisals of the situation greatly influence whether and when a recommended protective action is likely to be adopted [24][25][26][27].…”
mentioning
confidence: 99%